Mechanofluorochromism and mechanical force-triggered solid-state [2+2] photocycloaddition in α-cyanostilbene derivatives. (May 2022) - Huang, Jundan; Wei, Wenjing; Li, Bian; Liu, Tao; Chen, Xiaofang
Abstract: α-Cyanostilbene derivatives are known as fluorescent photochromic molecules that could be used to realize emission colour change or on/off switching via photo-induced isomerization or cycloaddition. Comparing with isomerization, photocycloaddition is less studied due to its critical molecular position and alignment requirement for molecular packing. In this work, biphenyl-based cyanostilbenic compounds 1 –3 were synthesized, which exhibit characteristic mechanofluorochromic (MFC) response behaviour. Under force stimuli, the luminescent colour has bathochromic shift from blue to green, together with the phase transition from crystal to amorphous state. Photochromic fluorescent response attributed to photo-induced [2 + 2] cycloaddition could take place instantly in amorphous state, rather than crystals. The MFC response can be successfully used to monitor the photoreaction process, giving rise to quantitative dimerized product. The single crystal structure of compound 2 revealed its photostable feature. The formation of excimers in ground amorphous state, together with the mechanical shearing, facilitates the occurrence of cycloaddition. Subsequently, the recovery process could be achieved thermally or under UV irradiation. Graphical abstract: Image 1 Highlights: Photo-[2+2] cycloaddition induced florescent responsetakes place in amorphous state, instead of crystalline state. Machanochromic response with a transformation from crystals to amorphous solid turns on the photoactivity of compounds. Machanochromic and photochromic response can be used to monitor the solid-state photoreaction process.